Family Law Effects on Divorce, Fertility, and Child Investment - Brown, Meta; Flinn, Christopher J.; Mullins, Joseph (Journal of Labor Economics, 2025)
To assess the child welfare impact of policies governing divorced parenting, such as child support orders, child custody assignments, and marital dissolution standards, one must consider their influence not only on the divorce rate but also on spouses’ fertility choices and child investments. We develop a model of fertility, parenting, and divorce, from which we derive estimates of parental preferences and a child cognitive ability production function, using data on parental time allocation, children’s cognitive attainment, and realized fertility and divorce. Family policies that reduce divorce are simulated to have significant negative impacts on both fertility and child development.